ANALISIS PEMANFAATAN ARTIFICIAL INTELLIGENCE (AI) OLEH GURU DALAM PEMBELAJARAN BAHASA INDONESIA DI MTS NEGERI 1 JENEPONTO: - - Fhatiha Hermaul, Nurul; M. Agus; Aco (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The main problem raised in this study is how to use artificial intelligence (AI) in Indonesian learning by teachers at MTs Negeri 1 Jeneponto?. The purpose of this research is to describe the use of artificial intelligence (AI) in Indonesian learning by teachers at MTs Negeri 1 Jeneponto. The type of research used is qualitative research designed using qualitative descriptive methods. This qualitative descriptive method is used to describe a phenomenon about the use of AI in Indonesian language learning with data collection techniques, namely direct interviews, direct observations, and documentation. The data that has been collected is analyzed with steps, namely reducing the data that has been collected, then drawing conclusions and interpretation, and triangulating to ensure that the data that has been analyzed and interpreted is in accordance with the needs of the research. Based on the results of this study, it can be concluded that the use of AI has been actively implemented by teachers, especially through platforms such as ChatGPT, Gemini, Canva, and Google Classroom. Teachers use AI in various aspects of learning, ranging from the preparation of teaching modules, the creation of evaluation questions, to digital classroom management. This utilization has been proven to provide significant benefits, such as efficiency of working time, increased teacher creativity, ease of access to learning resources, and increased student participation and interest in learning. The students' response to the use of AI was also quite positive, as seen from their enthusiasm during the learning process.